Self-consistent field theoretic simulations of amphiphilic triblock copolymer solutions: Polymer concentration and chain length effects - Han, X.-G.; Ma, Y.-H. (Condensed Matter Physics, 2014)
Using the self-consistent field lattice model, polymer concentration φP and chain length N (keeping the length ratio of hydrophobic to hydrophilic blocks constant) the effects on temperature-dependent behavior of micelles are studied, in amphiphilic symmetric ABA triblock copolymer solutions. When chain length is increased, at fixed φP, micelles occur at higher temperature. The variations of average volume fraction of stickers φcos and the lattice site numbers Ncols at the micellar cores with temperature are dependent on N and φP, which demonstrates that the aggregation of micelles depends on N and φP. Moreover, when φP is increased, firstly a peak appears on the curve of specific heat CV for unimer-micelle transition, and then in addition a primary peak, the secondary peak, which results from the remicellization, is observed on the curve of CV. For a long chain, in intermediate and high concentration regimes, the shape of specific heat peak markedly changes, and the peak tends to be a more broad peak. Finally, the aggregation behavior of micelles is explained by the aggregation way of amphiphilic triblock copolymer. The obtained results are helpful in understanding the micellar aggregation process. Використовуючи самоузгоджену польову ґраткову модель, вивчаються ефекти концентрацiї φ¯ P i довжини ланцюга N полiмера (при фiксованому вiдношеннi довжин гiдрофобних i гiдрофiльних блокiв) на температуро-залежну поведiнку мiцел в амфiфiльних симетричних ABA триблочних кополiмерних розчинах. Якщо довжина ланцюга зростає, при фiксованому φ¯ P , мiцели утворюються при вищiй температурi. Змiна середньої об’ємної долi стикерiв φ¯s co та числа вузлiв ґратки N ls co з температурою при мiцелярних корах залежать вiд N i φ¯ P , що вказує на залежнiсть агрегацiї мiцел вiд N i φ¯ P . Крiм того, якщо φ¯ P зростає, спочатку пiк виникає на кривiй питомої теплоємностi CV для переходу мономер-мiцела, i потiм додатково спостарiгаються на кривiй CV основний пiк, вторинний пiк, якi є результатом ремiцелiзацiї. Для довгого ланцюга при режимах промiжних i високих концентрацiй значно змiнюється форма пiку питомої теплоємностi, i пiк прямує до ширшого пiку. Накiнець, агрегацiйна поведiнка мiцел пояснюється способом агрегацiї амфiфiльного триблочного кополiмера. Отриманi результати є корисними для розумiння процесу агрегацiї мiцел.